A FOSM-BASED RELIABILITY ASSESSMENT OF STEAM GENERATOR TUBES UNDER CRACKING DEGRADATION - Francisco, Alexandre Santos; Berthou, Ronan (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Steam generator tubes are critical parts in the safety and operability of nuclear power plants. Thus, the degradation in steam generator tubes must be prevented. These tubes are subjected to the degradation mechanism of stress corrosion cracking, which is characterized by several uncertainties. The assessment of structural reliability of the steam generator tubes is essential for preventing the occurrence of failure events. In the present work, a study is carried out for assessing the structural reliability of the steam generator tubes containing cracks, by using first order second-moment (FOSM) concepts. The limit state function is based on a limit load model provided by Eletric Power Research Institute (2001), which describes the failure criterion. The applicability of the FOSM method as a methodology for predicting the reliability of steam generator tubes is checked by comparing results of calculated failure probability with ones obtained from Monte Carlo simulation. The FOSM method has provided a non-conservative reliability assessment for the steam generator tubes containing cracks, and are eligible for estimating the failure probability of this safety-critical structure.